Knowledge and practice regarding dengue and chikungunya: a cross‐sectional study among Healthcare workers and community in Northern Tanzania. Issue 5 (3rd April 2017) - Kajeguka, Debora C.; Desrochers, Rachelle E.; Mwangi, Rose; Mgabo, Maseke R.; Alifrangis, Michael; Kavishe, Reginald A.; Mosha, Franklin W.; Kulkarni, Manisha A.
Abstract: Objective: To investigate knowledge and prevention practices regarding dengue and chikungunya amongst community members, as well as knowledge, treatment and diagnostic practices among healthcare workers. Method: We conducted a cross‐sectional survey with 125 community members and 125 healthcare workers from 13 health facilities in six villages in the Hai district of Tanzania. A knowledge score was generated based on participant responses to a structured questionnaire, with a score of 40 or higher (of 80 and 50 total scores for community members and healthcare workers, respectively) indicating good knowledge. We conducted qualitative survey ( n = 40) to further assess knowledge and practice regarding dengue and chikungunya fever. Results: 15.2% ( n = 19) of community members had good knowledge regarding dengue, whereas 53.6%, ( n = 67) of healthcare workers did. 20.3% ( n = 16) of participants from lowland areas and 6.5% ( n = 3) from highland areas had good knowledge of dengue ( χ 2 = 4.25, P = 0.03). Only 2.4% ( n = 3) of all participants had a good knowledge score for chikungunya. In the qualitative study, community members expressed uncertainty about dengue and chikungunya. Some healthcare workers thought that they were new diseases. Conclusion: There is insufficient knowledge regarding dengue and chikungunya fever among community members and healthcare workers. Health promotion activities on these diseases based on Ecological Health Mode components to increase knowledge and improve preventive practices should be developed.